SWOT Analysis of Biomimicry for Sustainable Buildings – A Literature Review of the Importance of Kinetic Architecture Applications in Sustainable Construction Projects. Issue 8 (February 2019) - Bayhan, Hasan Gokberk; Karaca, Ece
Abstract: Biomimicry is a term to explain the use of genius in nature. It basically aims to use of resources in the most effective manner while satisfying human needs. Likewise, kinetic architecture implementations and biomimicry both tend to imitate the excellent mobility of nature and kinetic architecture implementations are somehow investigated in biomimicry studies. These two inspirational concepts of nature nested each other and were integrated over time contributing to the development of sustainable building system design. However, integration of biomimicry and kinetic architecture is essential to explain sustainable buildings and their certification systems. There is still lack of knowledge in the construction industry in terms of kinetic architecture and biomimicry practices since the concepts are dynamic and perceived to be complex by the industry practitioners. Moreover, traditional structure of the construction industry considering short term profits and project-based nature makes these concepts even more challenging for the projects. Hence, it is essential to apply strength, weakness, opportunity and threat (SWOT) analysis in biomimicry and kinetic architecture implementation so that construction industry practitioners might conduct projects more effectively and satisfy project requirements in sustainable building projects. Therefore, this study adopts SWOT as the research methodology and aims to guide construction professionals to better understand these concepts. Within this perspective, this study proposes five major strengths, namely the effective use of energy, higher prestige level, climate adaptation ability, enhancing comfort and higher value and rental costs, where weaknesses are higher initial or maintenance costs, lack of systems expertise, the need for coordination of different professions, special production requirements and complexity in design. Moreover, five major opportunities and threats are suggested as top management support, sustainability focused development strategy, technological improvements, the demand increase to the environmentally responsible buildings, incentives from the governmental bodies are opportunities; unfamiliar systems, system failures, difficulties in project financing, materials do not comply with standards, and market conditions, respectively. The study is expected to reinforce the link between the design and construction processes to apply the above-mentioned concepts in sustainable buildings.